Cerita Panji sebagai Repertoar Lakon Wayang Gêdhog Gaya Surakarta Telaah Struktur Teks, Makna dan Kaitannya dengan Pertunjukan - Rudy Wiratama (Jurnal Kajian Seni, 2020)
Panji stories which based on the romance-adventure of Panji, the crown prince of Jenggala who searches his lover, Galuh or Candrakirana, has inspired a vast range of art forms in Indonesia, from dances, songs to puppetry. Wayang gědhog is one of surviving art forms concerning Panji theme, born around 15th century and developed in Javanese courts until now, despite of its lack of popularity compared with the Mahabharata and Ramayana-themed wayang purwa. Wayang gědhog in two Javanese courts in Surakarta, Kasunanan and Mangkunagaran, has flourished time by time with their own unique characteristics, which are rarely known nowadays. This uniqueness wasn’t only caused by the past values of Panji stories’ setting contexts, but also related with some actual factors which are relevant in the era of those Javanese courts. This article would discuss about Surakartanese wayang gědhog’s development history, narrative structure, meanings and the relations between Surakartanese Panji-themed stories with its performance.